Estimating the cost of operating cancer registries: Experience in Colombia. (December 2016) - de Vries, Esther; Pardo, Constanza; Arias, Nelson; Bravo, Luis Eduardo; Navarro, Edgar; Uribe, Claudia; Yepez, María Clara; Jurado, Daniel; Garci, Luz Stella; Piñeros, Marion; Edwards, Patrick; Beebe, Maggie Cole; et al.
Highlights: 5 Colombian cancer registries completed a tailored CDC excel-based costing tool. Types of data collected, collection approach, and activities varied by registry. Average cost per case had threefold variation, US $41 to US $113 in 2013. Abstract: Background: Maintaining population-based registries requires adequate and sustained resources; however, to date there has been no systematic evaluation to identify the resource needs for cancer registration in most countries, including Colombia. A systematic assessment of the costs can quantify the funding required and identify processes to improve efficiency of cancer registries. Methods: The Centers for Disease Control and Prevention's (CDC's) International Registry Costing Tool ( IntRegCosting Tool) was tailored specifically for the Colombian registries and was used to collect resource use data from five regional population-based cancer registries: Barranquilla, Bucaramanga, Cali, Manizales, and Pasto. The registries provided cost data for the year 2013 and cancer cases corresponding to the year 2010. Results: We identified an almost threefold variation in the average cost per case (77, 932 to 214, 082 Colombian pesos or US $41 to US $113 in 2013) across the registries, but there were also substantial differences in data collection approaches, types of data collected, and activities performed. Cost per inhabitant varied between 95 and 415 Colombian pesos (US $0.05 to US $0.22). Between 20% and 45% of the total cost was due to fixed cost activities. Conclusions: The detailed economic information presented in this study constitutes a valuable source of activity-based cost data that registries can use to compare operations, assess key factors that lead to differences in cost per case, and identify potential approaches to improve efficiencies. Furthermore, the knowledge gained from studying the Colombian registries can help inform the planning and operations of other registries in the region.